Nurses’ experiences of presenteeist behaviors in the hospital - Lenícia Cruz Soares; Adrize Rutz Porto (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to understand nurses’ experiences regarding presenteeist behaviors in the hospital. Methods: a single holistic descriptive case study with a qualitative approach, with 32 nurses. Data were collected in three stages, through vignettes and in-depth individual interviews, audio-recorded and submitted to thematic analysis. The theoretical framework adopted was Christophe Dejours’ Psychodynamics of Work. Results: three topics emerged, revealing that the concept of presenteeism was not known among participants, but they recognized themselves experiencing presenteeist behaviors due to physical or psychological problems that, in some way, affected quality of work. The main reasons for presenteeist behavior were professional commitment and financial issues. Final Considerations: presenteeism manifested itself through physical distress, such as musculoskeletal pain, and psychological distress, such as burnout, arising from hospital work organization, seen as exhausting, marked by excessive demands, which can affect task performance, worker health and the quality of care provided.